Se:Maya:m / Constantine Claudius Embagos ... [et al.] - Embagos, Constantine Claudius; Arman, Haritz Aiman; Abang Rahabidin, Abang Akmal Syafiq; Ahmad, Afiqah (2024)
The Timber Youth Hub at University Seri Iskandar is conceived as a bold architectural statement that reflects the restless energy, creativity, and desire for self-expression inherent in today’s youth. The design concept, "Mirror Souls in Radicalism," seeks to challenge conventional norms by creating a structure that defies predictability and resonates deeply with the youthful spirit of rebellion and uniqueness. This hub is not just a building; it is a canvas of radical form, designed to captivate attention and provoke thought, offering a space where young minds can connect with their cultural heritage in a way that is both contemporary and meaningful. The Timber Youth Hub's narrative unfolds in a world where younger generations frequently view the past as irrelevant and disengaging. This project seeks to overturn that perception by creating a pavilion that is as much a symbol of youthful defiance as it is a vessel for cultural engagement. The radical design of the hub, with its unconventional forms and unpredictable elements, mirrors the desire of today’s youth for uniqueness and self-expression. The structure stands as a testament to the idea that history, when reimagined creatively, can be both inspiring and relevant.